The Nurcu Movement and Tafsir Risale-i Nur: Formation of Muslim Identity in the Midst of Modernization - Khamami, Akhmad Rizqon (Mashdar: Jurnal Studi Al-Qur'an dan Hadis, 2023)
This article discusses the Nurcu movement and Risale-i Nur amidst the process of modernization during Republican Turkey. The atheistic science adopted during the modernization absorbed Said Nursi’s concern. In attacking the philosophy of materialism and atheism, he resorted to an attempt to interpret the Qur'an, namely Risale-i Nur. Through the Risale-i Nur, a group of Said Nursi's followers came together into a social movement, which is known as the Nurcu movement. This article aims to reveal how Said Nursi faced modernity and posited the Nurcu movement in the midst of modernity. This research used a content analysis approach to the works written by Said Nursi, especially Risale-i Nur, as the main data, and supplementary data were gathered from studies conducted by scholars concerning Said Nursi, Risale-i Nur, and the Nurcu movement. In addition, reading on the intellectual context surrounding the emergence of Risale-i nur becomes a tool to comprehend the content of Risale-i Nur and the thoughts of the author. This research found that with the presence of Risale-i Nur, the followers of Said Nursi's teachings make Risale-i Nur a marker of group identity bringing with them tasks to seize science and modernity. Said Nursi's work is a modernist kind of interpretation of the Quran. Thus, in the midst of modernization and secularization in Turkey, Risale-i Nur offers Muslims an identity.